COUPLING OF ANATECTIC REACTIONS AND DISSOLUTION OF ACCESSORY PHASES AND THE SR AND ND ISOTOPE SYSTEMATICS OF ANATECTIC MELTS FROM A METASEDIMENTARY SOURCE - Zeng L.; Asimow P.D.; Saleeby J.B. (My University, 2005)
Advances in field observations and experimental petrology on anatectic products have motivated us to investigate the geochemical consequences of accessory mineral dissolution and nonmodal partial melting processes. Incorporation of apatite and monazite dissolution into a muscovite dehydration melting model allows us to examine the coupling of the Rb-Sr and Sm-Nd isotope systems in anatectic melts from a muscovite-bearing metasedimentary source. Modeling results show that (1) the Sm/Nd ratios and Nd isotopic compositions of the melts depend on the amount of apatite and monazite dissolved into the melt, and (2) the relative proportion of micas (muscovite and biotite) and feldspars (plagioclase and K-feldspar) that enter the melt is a key parameter determining the Rb/Sr and 87Sr/86Sr ratios of the melt. Furthermore, these two factors are not, in practice, independent. In general, nonmodal partial melting of a pelitic source results in melts following one of two paths in εNd-87Sr/86Sr ratio space. A higher temperature, fluid-absent path (Path 1) represents those partial melting reactions in which muscovite/biotite dehydration and apatite but not monazite dissolution play a significant role; the melt will have elevated Rb/Sr, 87Sr/86Sr, Sm/Nd, and εNd values. In contrast, a lower temperature, fluid-fluxed path (Path 2) represents those partial melting reactions in which muscovite/biotite dehydration plays an insignificant role and apatite but not monazite stays in the residue; the melt will have lower Rb/Sr, 87Sr/86Sr, Sm/Nd, and εNd values than its source. The master variables controlling both accessory phase dissolution (and hence the Sm-Nd system), and melting reaction (and hence the Rb-Sr systematics) are temperature and water content. The complexity in Sr-Nd isotope systematics in metasediment-derived melts, as suggested in this study, will help us to better understand the petrogenesis for those granitic plutons that have a significant crustal source component.